Mekanisme Vitamin C Menurunkan Stres Oksidatif Setelah Aktivitas Fisik - Junian Cahyanto Wibawa; Lilik Hera Wati; Muhammad Zainul Arifin (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2020)
The writing of this article aims to find out how the mechanism of vitamin C in reducing oxidative stress after physical activity. The method used is a systematic literature review. The result showed that vitamin C can inhibit oxidative stress after physical activity. Vitamin C is a water-soluble substance and it acts as chainbreaking antioxidant. It scavenges free radicals and reactive oxygen species (ROS), which are produced during metabolic process. Exercise can produce an imbalance between ROS and antioxidants, which leads to tissue damage related to oxidative stress. Vitamin C also acts as a supporting factor in several enzymatic reactions in the body and can increase components of the immune system. Because of the pivotal role of vitamin C in reducing free radical levels, this review article presents a characteristics and functions of vitamin C as an antioxidant to lessen the levels of free radicals which focused in exercise condition. It can be concluded that supplementation of vitamin c after physical activity can inhibit oxidative stress.